PENENTUAN SUHU DAN SUMBER KARBON TERBAIK PADA PERTUMBUHAN ISOLAT SBJ8 DALAM BIODESULFURISASI DIBENZOTIOFENA - Bagus Surya Adnyana, Gde Agung; Wayan Gunam, Ida Bagus; Dewi Anggreni, A. A. Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 4 (2016): Desember)
The determined of these research  were to knowing optimal of temperature  and carbon source of biodesulfurization isolate SBJ8. Isolate growth at Medium MSSF-TD with concentration of 200 ppm DBT in tetradecane which tested various temperature 37?C, 41?C, 45?C. The next step was to determine the best carbon source using glucose,  sucrose and citric acid. The result of experiment showed isolate SBJ8 temprature at 37?C and pH 7 with carbon source glucose. In condition SBJ8 could growth  (OD660) from 0,765,  and 0,411  with DBT degradation rate in tetradecane each 76,7%, and 63,4%. Keyword: biodesulfurization, SBJ8, dibenzothiophene, tetradecane.
Keywords: 119,